The seal and herring fisheries of Newfoundland [electronic resource] : together with a condensed history of the island - Carroll, Michael; Whitbourne, Richard, fl. 1579-1626. A discourse and discovery of New-found land. ([Montreal? : s.n.], 1873)
With: A discourse containing a loving invitation both honourable and profitable, to all such as shall adventure, either in person or purse, for the advancement of His Majesty's most hopefull plantation in the New-found land, lately undertaken / written by Captain Richard Whitbourne. Tables. Electronic reproduction. Mode of access: Internet. 44